Bullying di Tempat Kerja di Indonesia - Ika Adita Silviandari; Avin Fadilla Helmi (Buletin Psikologi, 2018)
Workplace bullying is one of an organizational phenomenon that has received a lot of attention from many parties, both academics, and practitioners. Workplace bullying is like an iceberg phenomenon. It exists but hard to be revealed and lifted to the surface. This phenomenon can be seen as practically and methodologically point of view. Practically, it is caused by passivity and silent act from the victim or bullying eyewitnesses, and methodologically, it hasn’t found the standard concept of workplace bullying which causing lack of workplace bullying research. In this article, the author tries to review the workplace bullying’s concepts and constructs, starting by reviewing the problem of definition, including type, frequency, & duration of bullying actions, and considering the role of workplace cultural values and norms in influencing the perception of bullying behavior.